2019
DOI: 10.1002/ams2.402
|View full text |Cite
|
Sign up to set email alerts
|

Bad blood: A coagulopathy associated with trauma and massive transfusion review

Abstract: Coagulopathy in trauma patients is a known contributor to death due to hemorrhage. In fact, it seen as frequently as 35% of the time. The complexity of the coagulopathy pathway requires a deliberate and planned approach. The methods used to assess and detect if a patient is coagulopathic remain challenging, but tools have been developed to assist the practitioner to effectively manage and even quickly reverse the coagulopathy. The purpose of this review is to educate trauma and emergency medicine staff on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…In addition, this type of problem solving may need to include a more detailed massive transfusion protocol. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, this type of problem solving may need to include a more detailed massive transfusion protocol. 23 24 …”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In isolated traumatic brain injuries, the hyperfibrinolytic state evoked by a brain injury was related to tissue factors released into the blood, microvessel failure, disruption of the blood-brain barrier, platelet-endothelial interaction, and platelet dysfunction. [18][19][20] These conditions activated the blood coagulation system and increased the consumption of blood coagulation factors. Additionally, the release of endogenous plasminogen activator was evoked and hyperfibrinolysis occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the release of endogenous plasminogen activator was evoked and hyperfibrinolysis occurred. [18][19][20] Biomarkers to predict progressive hemorrhagic brain injury in isolated traumatic brain injury have been reported reflecting these responses. 8,21 Nakae et al reported that D-dimer was an important biomarker to predict progressive hemorrhagic brain injury in isolated traumatic brain injury, reaching a peak at 3 h after injury before returning to baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations